2018
DOI: 10.18632/oncotarget.24856
|View full text |Cite
|
Sign up to set email alerts
|

Gene-specific methylation profiles in BRCA-mutation positive and BRCA-mutation negative male breast cancers

Abstract: Male breast cancer (MBC) is a rare disease. Due to its rarity, MBC research and clinical approach are mostly based upon data derived from female breast cancer (FBC). Increasing evidence indicate that on molecular level MBC may be an heterogeneous disease different from FBC.In order to investigate whether epigenetic signatures could define molecular subgroups of MBCs, we performed promoter methylation analysis of genes involved in signal transduction and hormone signalling in BRCA1/2 mutation-positive and -nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Furthermore, evidence of significant hereditary predisposition was found in this cohort (FH of breast cancer, BRCA2 mutations and NBPN, in 20.3%, 32.4%, and 15.5% of cases, respectively) which is line with published literature [26,27]. Furthermore, the clinical and pathological characteristic of the patient population are also similar to those previously published [3,21,28], which further validates our dataset.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, evidence of significant hereditary predisposition was found in this cohort (FH of breast cancer, BRCA2 mutations and NBPN, in 20.3%, 32.4%, and 15.5% of cases, respectively) which is line with published literature [26,27]. Furthermore, the clinical and pathological characteristic of the patient population are also similar to those previously published [3,21,28], which further validates our dataset.…”
Section: Discussionsupporting
confidence: 91%
“…Although the acquisition of epigenetic alterations, in general, and aberrant DNA methylation, in particular, is widely acknowledged as an early and relevant event in tumorigenesis [29], these have been seldom reported and with different purposes, in male BC [4,[18][19][20][21]. Kornegoor et al, examined promoter methylation of 25 genes in 108 male BCs using methylation specific multiplex ligation dependent probe amplification and concluded that promoter methylation was common in male BC and that high methylation status correlated with aggressive phenotype and poor outcome [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that AR promoter hypermethylation was associated with decreased AR expression in breast cancer cell lines ( 38 ), and that AR gene promoter methylation was higher in patients with wild-type BRCA1 /2 compared with mutated BRCA1 /2 in men diagnosed with breast cancer ( 39 ). In general, the data in the literature indicate that AR is associated with male breast cancer ( 39 ). The detection of hypermethylated AR in the brother with wild-type BRCA1 in the present study is consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%